2005
DOI: 10.1159/000090094
|View full text |Cite
|
Sign up to set email alerts
|

From Words to Actions: The Phonetics of Eigenlijk in Two Communicative Contexts

Abstract: This paper presents the results of an investigation into the distribution of phonetic variants of the Dutch discourse marker eigenlijk, combining phonetic and conversation analytic methods. The paper shows that the phonetic form of eigenlijkdepends to some extent on the sequential environment in which the item is used; moreover, it shows that in the case of two such environments, the forms of eigenlijk are representative of tempo and reduction patterns spanning entire turns or turn-constructional units. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(31 citation statements)
references
References 22 publications
2
26
0
3
Order By: Relevance
“…7 For example, of recurrently lacks a vowel portion, and when it does have a vowel, it is recurrently central rather than back. It can also be seen that eigenlijk occurs in its highly reduced, monosyllabic form, as previously described by Ernestus (2000), Keune et al (2005) and Plug (2005). With reference to the two subtypes of repair, of the 27 instances with editing terms, 15 are error repairs and 12 are appropriateness repairs.…”
Section: Editing Termssupporting
confidence: 62%
See 1 more Smart Citation
“…7 For example, of recurrently lacks a vowel portion, and when it does have a vowel, it is recurrently central rather than back. It can also be seen that eigenlijk occurs in its highly reduced, monosyllabic form, as previously described by Ernestus (2000), Keune et al (2005) and Plug (2005). With reference to the two subtypes of repair, of the 27 instances with editing terms, 15 are error repairs and 12 are appropriateness repairs.…”
Section: Editing Termssupporting
confidence: 62%
“…4 Previous research on the Dutch editing term eigenlijk 'actually' (Plug 2005) suggests that it is recurrently highly reduced, while most previous research on the phonetics of repetition has observed phonetic reduction rather than expansion, too, across a range of contexts (e.g. Fowler 1988, Bard et al 2000.…”
Section: Editing Terms and Repetitionmentioning
confidence: 99%
“…Furthermore, the unreduced and reduced variants may slightly differ in their pragmatic function (e.g. Plug, 2005). These acoustic and pragmatic differences between reduced and unreduced pronunciation variants may lead infants to store these variants as separate entries in their mental lexicons.…”
Section: Discussionmentioning
confidence: 99%
“…One speculative explanation for this latter result is that Dutch listeners may need to distinguish such forms, because the amount of phonetic reduction may be important in discourse (see, e.g., Plug, 2005). Since consonant lenition is grammaticalized in some languages (Shockey, 2003), it seems not far fetched to assume that reduction may have pragmatic purposes in other languages.…”
Section: Discussionmentioning
confidence: 99%